Implementation of Integrated Quality Management in Curriculum Development at MAN 1 Bandung - Mohamad Erihadiana; Wildan Baihaqi; Mimin Tjasmini; Supiyardi Supiyardi; Zul Andrivat (Khazanah Pendidikan Islam, 2023)
This research aims to implement integrated quality management in curriculum development at MAN 1 Bandung, establishing a significant link between the two through a thorough literature review and on-site observations. The impact of integrated quality management is palpable in the heightened relevance and meticulous review processes preceding curriculum formulation, ensuring the educational institution produces high-quality outputs. Employing a qualitative research methodology, the study delves into the intricate dynamics of integrated quality management and its transformative influence on curriculum development. Qualitative methods, including interviews, document analysis, and participant observations, enable an in-depth exploration of stakeholder perspectives and experiences, aiming to uncover the underlying mechanisms that enhance the overall quality of the curriculum. By critically analyzing qualitative data, the research identifies areas of improvement, effective practices, and challenges associated with integrating quality management principles, providing actionable insights for educational stakeholders. Ultimately, the study contributes to the academic discourse on curriculum development and guides ongoing efforts to optimize educational processes at MAN 1 Bandung through the integration of a robust quality management framework.